Exploring the Integration of ChatGPT in Pre-Service Teacher Education: Benefits, Challenges and Pedagogical Implications - David, Rowena May T.; Maroma, Adrian P. (Future Science / FSH-PH Publications, 2025)
This study examines the integration of ChatGPT in pre-service teacher education in the Philippines, focusing on its benefits, challenges, and potential impact on teaching practices. Using a qualitative research design, data were collected from 45 pre-service educators at Bulacan State University through an open-ended online survey. Thematic analysis revealed key challenges, including unfamiliarity with AI, concerns about accuracy and credibility, and risks of over-reliance on AI-generated content. Despite these concerns, participants recognized ChatGPT’s ability to enhance lesson planning, foster creativity, and support differentiated instruction. The findings highlight the need for structured AI training in teacher education programs, ethical guidelines for responsible AI use, and institutional support for effective AI integration. The study concludes that ChatGPT can serve as a valuable supplementary tool in teacher preparation, provided that educators receive adequate training and institutional backing. Future research should explore interactive methodologies, such as focus groups or classroom-based AI interventions, to gain deeper insights into its pedagogical applications.